Ligand reduction in variously substituted cerium (IV) tetrakis acetylacetone complexes by electrochemistry technique - Baghdad Science Journal (مجلة بغداد للعلوم, 2008)
In this work, substantial evidence was obtained for ligand reduction in cerium tetrakis acac complexes. Also, this ligand reduction of a negatively charged ligand proved to depend far less on the nature central metal than neutral ligands does. It is supposed that in Mz(acac)z complexes the charge is distributed evenly over the whole molecule. In this work these complexes were prepared and characterized by IR and CHN analysis to indicate the purities of these complexes. The electrochemistry techniques were shown as obtained for ligand reduction. This research was carried out at School of Chemistry and Molecular Science, Sussex University, U.K.